2020
DOI: 10.1080/0886022x.2020.1841655
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for post-parathyroidectomy hungry bone syndrome in patients with secondary hyperparathyroidism

Abstract: Background Hungry bone syndrome (HBS) following parathyroidectomy is associated with severe hypocalcemia and increased morbidity. This study aims to determine the incidence and risk factors of post-parathyroidectomy HBS in dialysis patients with secondary hyperparathyroidism (SHPT). Methods A retrospective cohort study was conducted, and medical records of patients with SHPT requiring parathyroidectomy between January 2014 and January 2020 were reviewed. HBS was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
(60 reference statements)
6
31
1
7
Order By: Relevance
“…The incidence of hypocalcemia after PTx ranges between 27% and 83%. 13,17,25 Our results were similar, where 57.6% of the HDG and 82.2% of the LDG developed hypocalcemia (< 2.0 mmol/l) within the first days. The administration of active vitamin D (calcitriol or alfacalcidol) reduces the incidence of hypocalcemia.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The incidence of hypocalcemia after PTx ranges between 27% and 83%. 13,17,25 Our results were similar, where 57.6% of the HDG and 82.2% of the LDG developed hypocalcemia (< 2.0 mmol/l) within the first days. The administration of active vitamin D (calcitriol or alfacalcidol) reduces the incidence of hypocalcemia.…”
Section: Discussionsupporting
confidence: 73%
“…10,11 Excessive preoperative levels of PTH, alkaline phosphatase (AP) and bone specific AP, low levels of calcium and albumin and young age were recently identified as risk factors for postoperative hypocalcaemia. [12][13][14] The administration of calcium supplements and active vitamin D to increase intestinal calcium absorption has long been standard in treating and preventing hypocalcemia after PTx. 11,[15][16][17] Moreover, bisphosphonates were effective lowering the incidence of HBS.…”
Section: Introductionmentioning
confidence: 99%
“…In total, five studies mentioned the results of age [ 5 , 14 , 15 , 18 , 19 ]. The statistical heterogeneity was high (I 2 =82%, p = 0.0002), and a random-effects model was used to perform a meta-analysis was performed on the unadjusted data.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies (including 13 groups of data) provided the results of preoperative ALP [ 2 , 5 , 8 , 13 , 14 , 17–22 ]. The statistical heterogeneity was high with I 2 =90% ( p < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…Old age, the size of the resected parathyroid glands, the preoperative serum iPTH level, and the preoperative serum alkaline phosphatase (ALP) level were found to be risk factors for SH after parathyroidectomy in patients with primary hyperparathyroidism [10][11][12][13]. Also, there is a study with controversial results that indicated young age was a risk factor for HBS [14]. Further, the preoperative iPTH and ALP levels were reported as risk factors for SH after parathyroidectomy in SHPT patients.…”
Section: Introductionmentioning
confidence: 99%